Accommodating Religious Practice at an Elementary School: A Case Study. (September 2022) - Frid, Carolyn; Lawlor Alexander, Sherry
Twelve Muslim intermediate student leaders at have shared their request for afternoon prayer space with Ms. Lidd, their white principal. Aware of the school board mandate to nurture the identity of students and build social capital through bridging opportunities, Ms. Lidd reviewed the policy for religious accommodations in schools. Principal Lidd takes the request to the School Improvement Committee. The accommodation is supported, plans to make space for afternoon prayer begins, and staff are informed of the accommodation for a prayer space. In this efficient response as a culturally responsive school leader (CRSL), Principal Lidd suddenly finds herself in conflict with staff. How will the principal navigate this resistance while ensuring the religious accommodation is met? How will she lead the staff toward developing culturally responsive practice?